Psilocybin administered following extinction sessions does not affect subsequent cocaine cue reinstatement in male and female rats and mice - Pohořalá, Veronika; Kuchař, Martin; Spanagel, Rainer; Bernardi, Rick E. (Neuroscience, 2024)
There are currently no pharmacological treatments for cocaine use disorder. Recently there has been a great deal of interest in the potential of psychedelic drugs such as psilocybin to treat psychiatric disorders. Human studies have indicated that a single administration of psilocybin can have long-lasting effects. Few preclinical studies have examined a role for psilocybin in addiction models. The goal of the current study was to determine whether psilocybin would enhance extinction following cocaine self-administration in male and female mice and rats and thus result in an attenuation of cue-induced drug-seeking. In experiments in mice, 16 female and 19 male mice underwent 8d of cocaine self-administration (0.5 mg/kg/infusion) and extinction training. Immediately following extinction trials, mice were injected with vehicle or 1.0 mg/kg psilocybin. Following the conclusion of extinction training, mice were tested for cue-induced reinstatement. In experiments in rats, 24 female and 23 male rats underwent 15d of cocaine self-administration (0.8 mg/kg/infusion) and extinction training. Immediately following extinction trials, rats were injected with vehicle, 1.0 mg/kg psilocybin, or 2.5 mg/kg psilocybin. Following the conclusion of extinction training, rats were tested for cue-induced reinstatement. Psilocybin administered following extinction trials had no effect, as both female and male mice and rats demonstrated significant cue-induced reinstatement. These data suggest that psilocybin is ineffective at altering cocaine-seeking behavior in the paradigm and doses used in the current study. It remains to be seen whether treatment with psilocybin under different conditions may be useful in the long-standing goal of finding pharmacotherapies to treat CUD.
Online verfügbar: 3. September 2024, Artikelversion: 10. September 2024
Gesehen am 25.11.2024